2016
DOI: 10.1245/s10434-016-5637-x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathology-Based Preoperative Risk Score to Predict Locoregional Residual and Distant Disease and Survival for Incidental Gallbladder Cancer: A 10-Institution Study from the U.S. Extrahepatic Biliary Malignancy Consortium

Abstract: Background This study was designed to develop a more robust predictive model, beyond T-stage alone, for incidental gallbladder cancer (IGBC) for discovering locoregional residual (LRD) and distant disease (DD) at reoperation, and estimating overall survival (OS). T-stage alone is currently used to guide treatment for incidental gallbladder cancer. Residual disease at re-resection is the most important factor in predicting outcomes. Methods All patients with IGBC who underwent reoperation at 10 institutions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
57
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 26 publications
9
57
1
5
Order By: Relevance
“…Lymphovascular invasion has been shown to be a surrogate for an aggressive malignant phenotype in GBC. 21, 22 Because lymphovascular invasion can be pathologically examined following cholecystectomy or with a preoperative (laparoscopic, endoscopic, or percutaneous) biopsy, it may be a useful tool in the selection of jaundiced GBC patients for radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion has been shown to be a surrogate for an aggressive malignant phenotype in GBC. 21, 22 Because lymphovascular invasion can be pathologically examined following cholecystectomy or with a preoperative (laparoscopic, endoscopic, or percutaneous) biopsy, it may be a useful tool in the selection of jaundiced GBC patients for radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ethun et al recently published the Gallbladder Risk Score (GBRS) based on univariate significance of LVI, PNI, T-stage and grade (11). This was the first study to propose a prognostic score to predict RD in incidental gallbladder cancer and prompted investigation of a preoperative model within our data.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of regional lymph nodes, while also prognostic, is not routinely available with the cholecystectomy specimen and unknown until re-operation and staging (10). Utilizing only factors available from the pathology report from the original cholecystectomy, a recent study found univariate associations between T stage, grade, lymphovascular invasion (LVI), and perineural invasion (PNI) with loco-regional residual disease, distant residual disease and overall survival (11). Preoperative prediction of residual disease has the potential to impact patient management and selection for modified treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…1118,23 In addition, LVI has been associated with other poor prognostic factors, such as poorly differentiated pathology, increased preoperative serum carcinoembryonic antigen levels, and lymph node metastasis. 11,16,24 Several studies have proposed using LVI as an independent risk factor, in lieu of lymph node involvement, to help guide prognosis and adjuvant treatment decisions, especially for diseases where lymph node status often cannot be deter-mined.…”
Section: Discussionmentioning
confidence: 99%
“…1118 Our group recently proposed a novel staging system for distal cholangiocarcinoma based on tumor size and LVI status, which better differentiated patient survival compared with the current AJCC T-stage system. Although lymph node involvement is a known poor prognostic factor, its prognostic value is limited in some malignancies due to low lymph node yields during resection.…”
mentioning
confidence: 99%